(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This article reviews the context of the Hygieia’s marble head recently found in Gortys. It mostly wants to give a general picture of building different phases, from a stratigraphic and chronological point of view. Attention is given to the last campaigns of excavations, which interested the eastern area of the bath complex. The article further describes the wall in which the sculpture was found and the comparisons with other similar structures in the site of Gortys, with particular attention to the building technique.